Enhancing Stability in Single-Phase PLLs: Incorporation of RoCoF Signal in Virtual Orthogonal Signal Construction - Abusorrah, Abdullah M.; Sepahvand, Hamed (IEEE transactions on industrial electronics (1982), 2024)
Single-phase ( 1φ ) phase-locked loops (PLLs) suffer from an oscillatory, time-periodic nature that contributes to the degradation of their stability. This is primarily due to the lack of two independent input signals, which necessitates generating a virtual orthogonal signal for transferring information to the dq frame. To mitigate this stability issue, this work proposes incorporating a factor of the rate of change of frequency in the construction of the virtual orthogonal input signal in 1φ PLLs. The effectiveness of this concept is verified through two case studies on the inverse Park PLL and synthesis circuit PLL.